Databases of information on the mite families Ologamasidae and Rhodacaridae (Mesostigmata: Rhodacaroidea): unlocking taxonomy, geographical distribution, and habitats - Barros, Ávyla Régia De Albuquerque; Moraes, Gilberto José De; Castilho, Raphael De Campos; Halliday, Bruce (Zootaxa, 2026)
Databases of information on the taxonomy, geographic distribution, and habitat of mites in the families Ologamasidae and Rhodacaridae are now freely available online. They provide data on 473 species of Ologamasidae and 162 species of Rhodacaridae. Most species of Ologamasidae were described from the Neotropical (33%) and Australasian (29%) ecozones. Most species of Rhodacaridae were described from the Afrotropical (36%) and Palaearctic (34%) ecozones. More than 75% of species in both families were described from specimens collected from soil.